The role of sodium surface species on electrochemical promotion of catalysis in a Pt/YSZ system: The case of ethylene oxidation - Naimah, Ibrahim; Poulidi, Danai; Metcalfe, Ian S. (Elsevier Inc., 2013)
Link to publisher's homepage at http://www.elsevier.com/